Gen Z Muslim Women's Consumptive Behavior in Following Muslim Fashion Trends on Social Media - Risma Fatma Sari; Finny Ligery; M. Agus Mushodiq (Journal of Contemporary Applied Islamic Philanthropy, 2026)
Purpose: As the Muslim fashion trend in Indonesia develops, clothing is no longer just a covering for the genitals but has become a symbol of identity, lifestyle, and social status, especially for Gen Z Muslim women. The Muslim fashion trend that has mushroomed in society through social media has triggered the consumer behavior of Gen Z Muslim women, which is certainly not in accordance with Islamic principles, namely the prohibition of isrāf and tabżīr. Through this study, the author wants to analyze the influence of Muslim fashion trends on the consumer behavior of Generation Z Muslim women through social media marketing. Methodology: This study used a quantitative approach with path analysis. The population in this study was Gen Z Muslim women, whose sample size was determined using the Lemeshow formula and respondents were determined using purposive sampling. There were 96 respondents, aged 17-28, who were active on social media and frequently purchased Muslim fashion products at least once or three times a week. Findings: This study provides results that Muslim fashion trends and social media marketing have a significant direct influence on the consumer behavior of Gen Z Muslim women. Furthermore, there is an indirect influence of Muslim fashion trends on Gen Z Muslim women's consumer behavior through social media marketing. Meanwhile, social media marketing through Muslim fashion trends has no significant influence on Gen Z Muslim women's consumer behavior. The variables included in this study contributed 32% of the influence on the consumer behavior of Gen Z Muslim women, the rest is influenced by various factors both internally and externally.